Baśnie Andersena oczyma współczesnych przedszkolaków - Strugińska, Karolina (Acta Universitatis Lodziensis. Folia Litteraria Polonica, 2008)
The article describes observations concerning a reception of H. Ch. Andersen s fairy-tales by contemporary children. An authoress asserts that realistic and sometimes cruel plots created in 19#1 century, deprived of therapeutical value (according to the B. Bettelheim s conception), seem to be unsuitable for children at early age. The thesis is supported by an unofficial survey carried out at two nursery schools among children aged 4-6 , who were talking to the authoress about their fillings just after reading #The fairy-tales . The analysis of Andersen s tales (based on a model of literary work created by R. Ingarden) shows how difficult it is for small children to follow to these stories on every three levels of composition. The article raises questions such as a language misunderstandings, a complicated metaphors and archaic elements o f the world presented an excessively negative emotions connected with the texts.